The Effect of Career Development and Work Life Balanced on Employee Job Satisfaction Tunas Daihatsu Bengkulu City - Marliza Ade Fitri; Gita Revina Meilanda; Herwan Mdk (UNIVED Press, 2023)
This research is based on the importance of employee job satisfaction in achieving company goals. Factors that can influence employee job satisfaction include Career Development and Work-Life Balance. The aim of this study was to determine the effect of Career Development and Work-Life Balance on the job satisfaction of Tunas Daihatsu employees in Bengkulu City. This study adopts a quantitative approach. Quantitative research is a systematic and structured research method conducted from the beginning to the end of the research process